Material returns: cultures of valuation, biofinancialisation and the autonomy of politics - Lilley, Simon; Papadopoulos, Dimitris (Sage, 2014)
The ascent of biofinancialisation since the 1980s brought with it a culture of valuation that spread well beyond financial markets and came to pervade everyday life, subjectivity, ecology and materiality. At the same time, and as a response to the social conflicts of the previous decades, value production shifts to incorporate the extended lifeworld of working people, their networks of sociality and the commons. The article examines the conflicts that emerge from the friction of the prevalent cultures of valuation and the extensive embodiment of value production and argues that biofinancialisation alters the very material infrastructure of bodies and forms of life. What is the autonomy of politics when biofinance becomes molecularised in code and in matter?